2022
DOI: 10.1016/j.jhin.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection methods against SARS-CoV-2: a systematic review

Abstract: Background The novel SARS-CoV-2, responsible for the most recent pandemic faced by humanity, has become a global crisis causing millions of deaths. The virus is transmitted by inhalation of infectious particles suspended in the air, direct deposition on mucous membranes and indirect contact via contaminated surfaces. Therefore, disinfection methods that can halt such transmission are important in this pandemic and in future viral infections. Aim Highlight the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 92 publications
(179 reference statements)
0
52
0
Order By: Relevance
“…The coronavirus disease-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made people attend to means and tools to inactivate airborne viruses [ 1 , 2 ]. Ultraviolet C (UVC) irradiation is getting a lot of attention as a means to disinfect pathogens in public spaces [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made people attend to means and tools to inactivate airborne viruses [ 1 , 2 ]. Ultraviolet C (UVC) irradiation is getting a lot of attention as a means to disinfect pathogens in public spaces [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although early on, the consensus pointed to direct contact and large droplets as the main source of infection, there is now growing evidence that the virus is transmitted by aerosols, 1 which might be even the main route of transmission 2 . Aerosols, as the major transmission route, better explains the superspreading events and the large proportion of infections generated from asymptomatic people 3 . Small aerosol particles can be suspended and travel through the air.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Aerosols, as the major transmission route, better explains the superspreading events and the large proportion of infections generated from asymptomatic people. 3 Small aerosol particles can be suspended and travel through the air. In the case of SARS‐CoV‐2, it was shown that they can remain viable for 3 h and float for several hours.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we examined an iodine and polyvinyl acetate (PVAc) composite system as surface coating material. Iodine is a well-known as a potential oxidant to inactivate microbes and viruses. , For long-term inhibition of virus transmission, surface coatings should remain stable, and the coating layer should be water-resistant. While most oxidizing reagents are highly soluble in water, iodine has relatively poor water solubility.…”
Section: Resultsmentioning
confidence: 99%